The nonprofit board answer book a practical guide for board members and chief executives. (Jossey-Bass : BoardSource, 2012)
"An essential guide to good governance for board leaders at all levels of experience and expertiseThis third edition of the bestselling book for nonprofit board members and professionals offers a thoroughly revised and updated resource that answers the most-commonly asked question on board governance. The book covers such topics as board structure and process, board member recruitment and orientation, board-staff relations, and financial management. This new edition includes updated information on topics that have recently increased in importance including new Form 990; dealing with the financial crisis, risk management, and mergers. Shows executives and board members how to be more effective, meet difficult situations head-on, and deal with commonplace challenges with confidence Topics include information on the viability of for-profit ventures, board retreats, board diversity, fundraising, financial oversight, strategic thinking, and the use of technology From Boardsource the premier resource for practical information, tools, best practices, training, and leadership development for board members of nonprofit organizations worldwide Offers insight gained from the BoardSource Governance Index Survey, hundreds of board self-assessments, and questions and challenges heard by BoardSource from thousands of nonprofit leaders"--